Biosorption of heavy metals by Pseudomonas species isolated from sugar industry. (September 2016) - Naz, Tayyaba; Khan, Muhammad Daud; Ahmed, Iftikhar; Rehman, Shafiq ur; Rha, Eui Shik; Malook, Ijaz; Jamil, Muhammad
Heavy metal-resistant bacteria can be efficient bioremediators of metals and may provide an alternative or additional method to conventional methods of metal removal. In this study, 10 bacterial isolates were isolated from soil samples of a sugar industry, located at Peshawar, Pakistan. Morphological, physiological, and biochemical characteristics of these isolates were observed. Sequence analysis (16S ribosomal RNA) revealed that isolated strains were closely related to the species belonging to the genera Pseudomonas, Arthrobacter, Exiguobacterium, Citrobacter, and Enterobacter . Bacterial isolates were resistant with a minimum inhibitory concentration (500–900 ppm) to lead ion (Pb 2+ ), (500–600 ppm) nickel ion (Ni 2+ ), (500–800 ppm) copper ion (Cu 2+ ), and (600–800 ppm) chromium ion (Cr 3+ ) in solid media. Furthermore, biosorption of metals proved considerable removal of heavy metals by isolated metal-resistant strains. Pseudomonas sp. reduced 37% (Pb 2+ ), 32% (Ni 2+ ), 29% (Cu 2+ ), and 32% (Cr 3+ ) and was thus found to be most effective, whereas Enterobacter sp. reduced 19% (Pb 2+ ), 7% (Ni 2+ ), 14% (Cu 2+ ), and 21% (Cr 3+ ) and was found to be least effective. While average reduction of Pb 2+, Ni 2+, Cu 2+, and Cr 3+ by Citrobacter sp. was found to be 24%, 18%, 23%, and 27%, respectively, among recognized species. This study revealed that Pseudomonas sp. may provide a new microbial community that can be used for enhanced remediation of contaminated environment.